Podocyte purinergic P2X4 channels are mechanotransducers that mediate cytoskeletal disorganization - Forst, Anna-Lena; Olteanu, Vlad Sorin; Mollet, Géraldine; Wlodkowski, Tanja; Schaefer, Franz; Dietrich, Alexander; Reiser, Jochen; Gudermann, Thomas; Schnitzler, Michael Mederos y; Storch, Ursula (Journal of the American Society of Nephrology, 2016)
Podocytes are specialized, highly differentiated epithelial cells in the kidney glomerulus that are exposed to glomerular capillary pressure and possible increases in mechanical load. The proteins sensing mechanical forces in podocytes are unconfirmed, but the classic transient receptor potential channel 6 (TRPC6) interacting with the MEC-2 homolog podocin may form a mechanosensitive ion channel complex in podocytes. Here, we observed that podocytes respond to mechanical stimulation with increased intracellular calcium concentrations and increased inward cation currents. However, TRPC6-deficient podocytes responded in a manner similar to that of control podocytes, and mechanically induced currents were unaffected by genetic inactivation of TRPC1/3/6 or administration of the broad-range TRPC blocker SKF-96365. Instead, mechanically induced currents were significantly decreased by the specific P2X purinoceptor 4 (P2X4) blocker 5-BDBD. Moreover, mechanical P2X4 channel activation depended on cholesterol and podocin and was inhibited by stabilization of the actin cytoskeleton. Because P2X4 channels are not intrinsically mechanosensitive, we investigated whether podocytes release ATP upon mechanical stimulation using a fluorometric approach. Indeed, mechanically induced ATP release from podocytes was observed. Furthermore, 5-BDBD attenuated mechanically induced reorganization of the actin cytoskeleton. Altogether, our findings reveal a TRPC channel-independent role of P2X4 channels as mechanotransducers in podocytes.